Regional differences in digitalisation and their impact on young people’s status attainment in vocational education and training - Hickmann, Helen [Verfasser]; Detemple, Jonas [Verfasser]; Wicht, Alexandra [Verfasser] (My University, 2025)
„While many of the recent changes in the labour market are related to digitalisation, there is little knowledge about digitalisation’s impact on young people’s transitions from school to vocational education and training (VET). The current study addresses this research gap by examining the relationship between the level of regional digitalisation and young people’s status attainment when entering VET. The study uses data from the German National Educational Panel Study (NEPS), merged with a unique regional digitalisation indicator at the district level (NUTS-3). OLS regression models show that, on average, young people entering VET in highly digitalised regions secure occupations with a higher status than their counterparts in less digitalised regions. Notably, regional digitalisation has a particularly strong positive impact on males, while no differences in association are observed by school leaving qualifications. The results underscore the existence of a discernible regional digital divide among VET entrants in Germany.“ (authors‘ abstract; BIBB-Doku)

Die Digitalisierung hat anhaltende Auswirkungen auf den Arbeitsmarkt und die berufliche Bildung. Eine aktuelle Studie der BIBB-Nachwuchsgruppe BOR³ kann mit Daten des Nationalen Bildungspanels zeigen, dass junge Menschen in stark digitalisierten Regionen im Durschnitt Berufe mit höherem Status ergreifen, wobei insbesondere Männer von einem höheren Digitalisierungsgrad profitieren. Neben der Verbesserung lokaler Infrastrukturen, um der Abwanderung aus strukturschwachen Regionen entgegenzuwirken, ist auch die Förderung regionaler Mobilität notwendig, um Chancenunterschiede auszugleichen und den Zugang zu statushöheren Ausbildungsberufen zu ermöglichen. (BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.1.4 Regionalisierung; G 1.3.2.2 Übergänge; 370; Arbeitsmarkt; Berufsbildung; Digitalisierung; Regionale Disparität; Einflussfaktor; Berufseinmündung; Berufswahl; Beruflicher Status; Nationales Bildungspanel